PENGARUH GREEN INNOVATION DAN KINERJA KEUANGAN PADA COMPETITIVE ADVANTAGE DAN NILAI PERUSAHAAN TAHUN 2015-2020 - Vera Putri Fabiola; Hidayatul Khusnah (Media Mahardhika, 2022)
This study aims to test Green Innovation and Financial Performance on Competitive Advantage and Firm Value in manufacturing companies. This study uses secondary data, where secondary data is data obtained from the annual financial statements listed on the IDX during the 2015-2020 period. The sample in this study were 37 companies. In this study using purposive sampling method and in analyzing data using the WarpPLS 6.0 application. The results of the analysis show that Green Innovation has a positive and significant effect on Competitive Advantage. Meanwhile, Green Innovation has no effect on company value. Green Innovation has a positive and significant effect on financial performance. Meanwhile, Competitive Advantage has a negative and significant effect on financial performance. And financial performance has a positive and significant effect on firm value.